TUMBUHAN FAMILI ZINGIBERACEAE DALAM UPAKARA DAN UPAYA PELESTARIANNYA DI DESA KEDISAN KECAMATAN TEGALLALANG KABUPATEN GIANYAR - I Gusti Ayu Rai; Komang Tri Yanti (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2024)
The Hindu community in Bali is inseparable from various religious ceremonies. In every religious ritual, the community uses multiple types of upakara facilities which are seen as a symbolic communication process carried out between humans and God, for all His gifts. Upakara facilities come from biodiversity, one of which comes from plants. Plants from the Zingiberaceae family known as empon-empon plants are one of the upakara facilities used in every Yadnya ceremony. Research related to this utilization was conducted in Kedisan Village, Tegallalang District, Gianyar Regency. Based on the research results, it is known that there are 14 types of plants from the Zingiberaceae family that are used in the ceremony, namely jahe (Zingiber officinale), kunyit kuning (Curcuma domestica Val.), kencur (Kaempferia galanga), kecombrang (Etlingera elatior), temu ireng (Curcuma aeruginosa), temu lawak (Curcuma xanthorrhiza), temu kunci (Boesenbergia rotunda), temu giring (Curcuma heyneane), temu mangga (Curcuma amada), temu tis (Curcuma purpurascen Blume), temu gongseng (Kaempferia rotunda L.), temu agung (Curcuma aromatica), temu putih (Curcuma zedoaria Rocs.), dan lempuyang (Zingiber zerumbet). The use of Zingiberaceae plants as a means of ritual is so extensive that the local community balances it with conservation efforts carried out in the yard, planted in pots, and planted as an interlude in plantation areas, fields, and on the edge of rice fields. So in this case, the use of Zingiberaceae plants as a means of ritual is a local wisdom that contains conservation values.